On Translatibility from English into Arabic: Words and Beyond - Gadacha, Ali (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis paper is an attempt to investigate the current problems the students graduating in English at the ISLT are likely to encounter when setting out to render English into Arabic. My teaching experience with them was beneficial, albeit quite short (one year-long only, 2000-2001). The material gathered, on the other hand, was wide-ranging and, better still, so provocative that I readily agreed to venture onto dangerous ground.Studies in the past have often failed to delve deep into possible meanings and extend beyond traditional boundaries so as to assess the scope of words and explore the meaning potentials. Recent advances in the literature argue that translators should be sensitive to the losses and gains of cultural elements and assess the “weight” of these elements in the source text in order to bring about the same/similar effects.It is true that loss of meaning is inevitable and the transference to the translator’s language can only be approximate (Newmark 1988, 7). The current trend in translation theory is to explore situations to make it possible to transcend linguistic as well as cultural barriers. Translators will continue to reproduce only restricted facets of meaning so long as they do not vanquish ordinary processes of thought and approach the words in the SL text as units of discourse. I make no pretence at being able to offer definitive solutions. This account aims at identifying the potentially problematic areas in translating English into Arabic. The sense of new in this experience embodies a larger vision, apparently a different quality of recognition since the focal interest is laid on the interpretive weight of words as constituent parts of the act of communication.